Developing an Instrument to Measure Information Assurance Implementation for eGovernment using Goal Question Metric Approach - Utomo, Rio Guntur; Wills, Gary; Walters, Robert (Universitas Muhammadiyah Malang, 2021)
The eGovernment initiative is aimed to improve government services to the public by improving the quality and availability of services that can be accessed regardless of time and place. Consequently, the services must always be available at any time, and any threat to the information and systems should receive attention to ensure business continuity in the event of an incident. Therefore, in implementing eGovernment, information assurance (IA) must be considered. To determine the extent to which IA implementation status to protect eGovernment services in Indonesia, it is necessary to measure the implementation using an instrument. The measurement instrument was developed using the Goal Question Metric (GQM) approach. The developed instrument was then used in a case study to test its effectiveness in measuring the IA implementation. From the results of the case study, it can be concluded that the IA measurement instrument for eGovernment was proven to be effective within Indonesian context.